Menstrual Tracking, Fitness Tracking and Body Work: Digital Tracking Tools and Their Use in Optimising Health, Beauty, Wellness and the Aesthetic Self - Anna Friedlander (Youth, 2023)
Digital self-tracking tools can be part of body work to measure, monitor, and optimise progress towards idealised versions of the self. Fitness and calorie trackers are obvious examples but menstrual tracking apps, which can track a large range of bodily ‘symptoms’, can also be part of body work. In this article, I present accounts of young people’s menstrual and fitness tracking experiences from existing literature, illustrating how both types of trackers can function as part of their users’ body work. I interweave these stories with an autoethnographic account of my own embodied experiences with and through menstrual and fitness tracking apps. I explore the ways in which health, beauty, and wellness can become enmeshed in self-tracking practices; how emotions, stress, and sleep can become personal problems to solve; how tracking tools can make body work feel more ‘real’; and the mutual but asymmetrical shaping of digital tracking tools and their users. Though there is an existing body of work on young people’s experiences of digital self-tracking tools more generally (particularly health and fitness tracking tools), young people’s use of menstrual tracking apps is a relatively understudied phenomenon to date. The themes identified in this article point towards possible avenues for future research.